2022
DOI: 10.1038/s41598-022-13087-3
|View full text |Cite
|
Sign up to set email alerts
|

Islet cell replacement and transplantation immunology in a mouse strain with inducible diabetes

Abstract: Improved models of experimental diabetes are needed to develop cell therapies for diabetes. Here, we introduce the B6 RIP-DTR mouse, a model of experimental diabetes in fully immunocompetent animals. These inbred mice harbor the H2b major histocompatibility complex (MHC), selectively express high affinity human diphtheria toxin receptor (DTR) in islet β-cells, and are homozygous for the Ptprca (CD45.1) allele rather than wild-type Ptprcb (CD45.2). 100% of B6 RIP-DTR mice rapidly became diabetic after a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…To investigate if combined HCT and islet transplantation could rescue overtly diabetic recipients across the barrier of full MHC mismatch, we used B6 RIP-DTR mice ( Bhagchandani et al, 2022 ). These harbor the Ins2-HBEGF transgene and are homozygous for Ptprc a (CD45.1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate if combined HCT and islet transplantation could rescue overtly diabetic recipients across the barrier of full MHC mismatch, we used B6 RIP-DTR mice ( Bhagchandani et al, 2022 ). These harbor the Ins2-HBEGF transgene and are homozygous for Ptprc a (CD45.1).…”
Section: Resultsmentioning
confidence: 99%
“…Female and male B6 CD45.1 (Stock #: 002014), BALB/c (Stock #: 000651), and FVB (Stock #: 001800) mice 7–8 weeks old were purchased from The Jackson Laboratory (Bar Harbor, ME). B6 RIP-DTR mice were generated and maintained by our group ( Bhagchandani et al, 2022 ). Males were used at 16–20 weeks old, and females were used at 8–10 weeks old.…”
Section: Methodsmentioning
confidence: 99%
“…Others have shown that xenotransplantation of stem cell derived human beta cells into immune competent mice are fully rejected (no surviving beta cells) within one week (23). Allotransplantation of murine pancreatic islets into nonchemically induced diabetic mice with mis-matched MHC Class I also reject by 4-10 days (56,(65)(66)(67)(68)(69). In overtly diabetic NOD mice, syngeneic NOD islet grafts in the kidney capsule take longer to reject, approximately 8-12 days (54, 70-72).…”
Section: Discussionmentioning
confidence: 99%